Automatic simulation-based design and validation of robotic gripper fingers. Issue 1 (2022) - Ramasubramanian, Aswin K; Connolly, Matthew; Mathew, Robins; Papakostas, Nikolaos
Abstract: The design of robotic gripper fingers is a complex process and often requires significant effort and time. This paper investigates a method to automatically generate new iterations of the gripper finger design as well as to validate its performance in a simulation environment. A Computer-Aided Design (CAD) software platform and a physics-based simulation framework are deployed to work in tandem to redesign and validate an initial gripper finger design aiming at reducing the overall time and cost required for physical validation. The proposed approach is validated in a real robotic case scenario, performing a series of pick and place tasks.